Damage detection in wind turbine blades by using operational modal analysis. (May 2016) - Lorenzo, Emilio Di; Petrone, Giuseppe; Manzato, Simone; Peeters, Bart; Desmet, Wim; Marulo, Francesco
In this paper a vibration-based approach to identify a crack in a wind turbine blade is described and demonstrated numerically and experimentally. Operational modal analysis has been performed before and after a buckling test, and vibration data, gathered from some accelerometers placed along the blade, was used to monitor the integrity of the structure, since the modal parameters are directly influenced by the physical properties of the structures. Additionally a numerical prediction has been done both with a full-scale model and with a one-dimensional model. The results show that this approach is able to estimate successfully the presence of damage and a good numerical and experimental correlation has been found. Finally, some considerations regarding the rotation of the blade in the undamaged and damaged cases have been done.